Virtual Reality Simulator for the Training of Lumbar Punctures - Matthias Färber; Hummel, F; Gerloff, C; Heinz Handels (Methods of information in medicine, 2009)
OBJECTIVES: Lumbar puncture (LP) is performed by inserting a needle into the spinal canal to extract cerebrospinal fluid for diagnostic purposes. A virtual reality (VR) lumbar puncture simulator based on real patient data has been developed and evaluated. METHODS: A haptic device with six degrees of freedom is used to steer the virtual needle and to generate feedback forces that resist needle insertion and rotation. An extended haptic volume-rendering approach is applied to calculate forces. This approach combines information from segmented data and original CT data which contributes density information in unsegmented image structures. The system has been evaluated in a pilot study with medical students. Participants of two groups, a training and a control group, completed different first training protocols. User performance has been recorded during a second training session to measure the training effect. Furthermore user acceptance has been evaluated in a questionnaire using a 6-point Likert scale with eight items. RESULTS: Forty-two medical students in two groups evaluated the system. Trained users performed better than less trained users (an average of 39% successfully completed virtual LPs compared to 30%). Findings of the questionnaire show that the simulator is very well accepted. E.g. the users agree that training with such a simulator is useful (Likert grade of 1.5 +/- 0.7 with 1 = "strongly agree" and 6 = "strongly disagree"). CONCLUSIONS: Results show that the VR LP simulator gives a realistic haptic and visual impression of the needle insertion and enables new insights into the anatomy of the lumbar region. It offers a new way for increasing skills of students and young residents before applying an LP in patients.
Keywords: Attitude of Health Personnel; Computer Simulation; Curriculum; Education, Medical; Feedback, Sensory; Humans; Image Processing, Computer-Assisted; Imaging, Three-Dimensional; Internship and Residency; Needles; Phantoms, Imaging; Spinal Puncture; Tomography, X-Ray Computed; Torque; Touch; User-Computer Interface